Mandarin attrition among tertiary students - Yu, Zhonggen; Chan, Swee Heng; Abdullah, Ain Nadzimah (Universiti Putra Malaysia Press, 2013)
This study aimed at determining whether Mandarin language attrition occurs in terms of Chinese character recognition, word order, and writing ability after a two-month holiday. The methodology of the study is mainly quantitative, and the data were obtained through pre- and post- tests. Pre- and post- Mandarin tests were conducted among 65 participants. The results showed that slight attrition was found in Chinese character recognition, while serious attrition occurred in word order and writing ability. The reasons for the attrition were also discussed. The study suggested that more attention be paid to learning Chinese word order and writing and less to Chinese character recognition for Mandarin learners, especially in Malaysia.